Northeastern Beauty-care Female Workers in South India: Experiencing the 'Body', Economic Inclusion and Social Exclusion as Migrants. Issue 2 (December 2017) - Deori, Banti; Rajagopalan, Prema
This article analyses three issues: (i) female migration from northeastern states of India to two southern cities of India, Chennai and Bangalore, employed in the beauty-care sector; (ii) the broad socio-demographic characteristics of female migrants; and (iii) the role of social and cultural capital in inclusion and exclusion of these migrants in the two southern cities. The article discusses the migration process using an intersectionality approach and focuses on how women have become the central players in Migration Studies. The article explores the broad socio-demographic factors associated with their migrations and also examines the problems and harassment faced by the female migrants from northeastern states working in the beauty-care sector. The article advocates the analysis of migratory processes within the broader framework of gender, race, ethnicity and the changing labour market in urban regions of India.